INVESTIGATION OF SINGLE-PHASE FLOW CHARACTERISTICS IN A STAGGER PIN-FINS COMPLEX GEOMETRY - R. Shakir (Mustansiriyah University/College of Engineering, 2021)
The cooling equipment project must use electrical and electronic equipment because of the need to remove the heat generated by this equipment. Investigation; R-113 single-phase flow heat transfer; (50 x 50 mm2) cross-section and (5 mm) height; used in a series of stagger-square micro-pin fins. Inlet temperature of (25 °C); (6) Mass flow rate at this temperature, the recommended range is (0. 0025 -0.01 kg/sec) the inlet and outlet pressures are approximately (1-1.10 bar), and through (25- 225 watts) applied heat. The iterative process is used to obtain the heat flow characteristics, for example; the single-phase heat transfer coefficient is completely laminar flow developing, in this flow, guesses the wall temperature, guess the fluid temperature. The possible mechanism of heat transfer has been discussed.